2008
DOI: 10.1007/s00586-008-0763-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of seven preoperative prognostic scoring systems for spinal metastases

Abstract: Predicting prognosis is the key factor in selecting the proper treatment modality for patients with spinal metastases. Therefore, various assessment systems have been designed in order to provide a basis for deciding the course of treatment. Such systems have been proposed by Tokuhashi, Sioutos, Tomita, Van der Linden, and Bauer. The scores differ greatly in the kind of parameters assessed. The aim of this study was to evaluate the prognostic value of each score. Eight parameters were assessed for 69 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
245
2
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(270 citation statements)
references
References 20 publications
14
245
2
9
Order By: Relevance
“…The type of primary tumour was not found to be significantly associated with survival in their study. Leithner et al [18] concluded from their retrospective study comparing seven similar scoring systems that the original Bauer score and a modified Bauer score without scoring for pathologic fracture were practicable and highly predictive for outcome and survival.…”
Section: Discussionmentioning
confidence: 99%
“…The type of primary tumour was not found to be significantly associated with survival in their study. Leithner et al [18] concluded from their retrospective study comparing seven similar scoring systems that the original Bauer score and a modified Bauer score without scoring for pathologic fracture were practicable and highly predictive for outcome and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Leithner et al [14] studied seven different scoring systems that predict survival in metastatic spinal cancer cases. They concluded that Bauer and modified Bauer systems score best among the seven studied in terms of accuracy of prediction.…”
Section: Discussionmentioning
confidence: 99%
“…These models employ different sets of prognostic factors such as performance score, primary tumor and the presence of visceral metastases to stratify patients with SBM according to survival risk, enabling clinicians to select a more appropriate treatment. Several studies have been undertaken to assess the prognostic value of these models and the factors being used [12,13]. The aim of this systematic review was to identify prognostic factors that are associated with survival in patients with spinal bone metastases in order to help guide development of predictive models.…”
Section: Introductionmentioning
confidence: 99%